La trama filosofica della Dichiarazione universale sulla Bioetica e i diritti umani: autonomia, dignità, vulnerabilità - Emilia D’Antuono (Laboratorio dell'ISPF, 2017)
The philosophical frame of the Universal Declaration on Bioethics and Human Rights: autonomy, dignity, vulnerability. Among the many different aspects of the Declaration (Unesco, 2005), some conceptual perspectives are now crucial in the international bioethical and biolegal debate. Particularly relevant is the link between notions like dignity, autonomy, vulnerability and responsibility. Even though they have different historical-philosophical origins, in the Unesco text they show reciprocal implications, which refer to the construction of a renewed semantics of personhood. Just as much relevant is the necessity of giving new meaning to the notion of universality. The Declaration suggests a perspective of inclusive universality, capable of embracing plurality. It also points out the practice of dialogue as the instrument for recognising diversities and for promoting the democratic participation in public debate, also through the dissemination of bioethics education programs.